Synthesis, Characterization and Biological Evaluation of Fe(III) and Cu(II) Complexes with 2,4-Dinitrophenyl hydrazine and Thiocyanate Ions - Manimaran, P.; Balasubramaniyan, S. (Asian Journal of Chemistry, 2019)
The metal complexes of Fe(III) and Cu(II) were prepared by using 2,4-dinitrophenyl hydrazine (DNPH) and thiocyanate (SCN) with stirrer refluxed for about 6 h. The prepared Fe(III) and Cu(II) complexes were characterized by elemental analysis, molar conductance, magnetic susceptibility and electronic spectrum, FT-IR spectral studies. The result suggested the octahedral geometry for Fe(III) and Cu(II) complexes. Powder X-ray diffraction indicate the crystalline nature of the metal complexes. The antimicrobial activities of the Fe(III) and Cu(II) complexes were tested with various micro organisms by disc diffusion method. The antimicrobial results indicate that the metal complexes are highly active with compared to the free ligand. The in vitro antioxidant activity of the free ligand and its metal complexes was assayed by radical scavenging activity (DPPH). The result proposed that Fe (III) and Cu(II) complexes exhibited strong antioxidant activity than that of the ligand.